Management Strategy of Superior Programs to Create the Image of Private Elementary Schools: A Case Study at SD Muhammadiyah Condongcatur - Bekti Yuaningsih; Enung Hasanah; Sukirman Sukirman (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Schools that facilitate talents and interests are still limited, and the management of flagship programs is not yet optimal. The effectiveness of implementing flagship programs still needs to be improved, and there is competition among schools in promoting themselves to attract students. This research aims to describe the management strategies of flagship programs to create the image of private elementary schools. The research uses a qualitative approach of case study type with data analysis using the Miles and Huberman model with the help of the ATLAS.ti 9 application. The research results show the management strategy for managing flagship programs to create the image of elementary schools thru the stages of strategy formulation, strategy implementation, and strategy evaluation that are interrelated. In the strategy formulation stage, the school conducts a current needs analysis, designs flagship programs, prepares the school budget, develops publication and branding strategies, and plans resources. The strategy implementation stage includes the intensive execution of flagship programs, utilization of school facilities, publication of student achievements, administration of flagship program achievements, and motivation from leaders. The evaluation stage of the strategy involves communicating the progress of the flagship program, considering feedback and suggestions, taking corrective actions, and innovating programs with low interest. The implementation of all stages of the management strategy for the flagship program at SD Muhammadiyah Condongcatur has resulted in a positive school image, including its existence in the community, high parental trust in the school, the quality of the flagship program, student enrollment exceeding the quota each year, and numerous student achievements.